Referral to specialist physiotherapists in the management of whiplash associated disorders: Perspectives of healthcare practitioners. (April 2018) - Bandong, Aila Nica; Leaver, Andrew; Mackey, Martin; Sterling, Michele; Kelly, Joan; Ritchie, Carrie; Rebbeck, Trudy
Abstract: Background: Guidelines for whiplash associated disorders (WAD) recommend early referral to specialists (e.g. specialist physiotherapists) of people who are not recovering. This recommendation is a key component of a proposed clinical pathway of care for WAD. Objective: To explore healthcare practitioners' opinions about referral to specialist physiotherapists of people with WAD at high risk of non-recovery. Design: Qualitative descriptive study. Methods: Six focus groups were conducted among primary care allied-health practitioners (n = 16) and specialist physiotherapists (n = 12) in New South Wales and Queensland, Australia. Discussions were audio recorded and transcribed for thematic analysis. Results: Ten themes were generated from analysis. Practitioners appeared to have good knowledge of indicators for referral; however, referrals were often made to the medical practitioner, less commonly to specialist physiotherapists. There was general support for referral to specialist physiotherapists, which was deemed as a viable alternative for people who are not recovering. Practitioners, however, had differing views about the attributes of a specialist physiotherapist and referral timeframe. A number of factors have been identified to influence the referral process and practitioners expressed specific expectations of the desired outcomes of referral as well as considerations for specialist management approaches. There was strong support for a collaborative approach in management that involved the referring practitioner. Conclusion: Results support the feasibility of referral to specialist physiotherapists despite limited uptake in practice and recognised barriers to referral. These findings have implications for further study and adopting strategies to facilitate effective implementation and translation of the proposed pathway into primary care practice. Highlights: Referral to specialist physiotherapists is well-supported. Generalists have high expectations of the referral process. Shared-care approach involving the referring practitioner facilitates referral. Significant barriers to overcome include clarification of roles and lack of access.